THE IMPLEMENTATION OF GENRE BASED APPROACH IN TEACHING WRITING - Septa Marwah Kamaliah; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2022)
This paper reports the implementation of Genre Based Approach in teaching writing. The research was conducted at Junior High School in Bandung. The subjects of this research were the seventh grade students of junior high school. The data were obtained from observation. Then, the data was analyzed descriptively. The researchers used descriptive qualitative. The findings revealed that there are four stages in implementing Genre based Approach in teaching writing such as building knowlede, modelling, joint construction and individual construction. The data also showed that students’ writing skill were developed after being taught by Genre based Approach. Keywords:  Students’ Difficulties, Genre Based Approach, Teaching Writing